SAINS DALAM PERSPEKTIF FILSAFAT ISLAM - Zulkarnain Zulkarnain (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2019)
Philosophical footing unlike modern Islamic science is to be distinguished from the philosophical foundation of Islamic science. Indeed, the main concern of the notion of Islamic science is closely related to the basic philosophy of science issues is growing and is recognized today including science paradigms and methodologies developed in the modern world that is more influenced by the thinking paradigm of the modern secular Western philosophy. This implies bias in epistemology and axiology which, between science and moral paradigm developed in Islam. In the practical level of science that was developed to be dried from a religious touch, as a result of these conditions afflict various disciplines of knowledge that has been studied by Islamic Philosophy. Therefore, Muslims increasingly need to differentiate between Islam and science that is not Islamic. Today, not many intellectual issues are more important to the contemporary Islamic world beyond the relationship between Islamic Philosophy and modern science.